Systematic Literature Review: Green Marketing dan Green Trust - Nisaa, Verselly; Ravelby, Thesa Alif; Permata, Shintya Dwi (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2025)
The purpose of this systematic literature review (SLR) from 2017 to 2021 is "to see which parts are used by researchers in articles", "Who are the top authors in this field". This research uses the PRISMA method. This research is about green marketing and green trust. This study found 9216 articles in the search using Science Direct and the help of VOSviewer and Miscrosoft Excel applications then filtering and selection selected 66 articles for analysis. The findings show that based on this review, the number of publications on green marketing and green trust per year has increased and shows the importance of this issue. Furthermore, based on this review, there are top ten authors with the most number of articles published on green marketing and green trust. And from this review, there are 17 journals with further publications on green marketing and green trust. Based on this review, the top journal with the highest number of citations is shown in Journal of Business Research with 76149 citations. The most frequently used keywords in the field of Green Marketing and Green Trust in consumer behavior are 5487